Implementasi Konsep GLAM dalam Pelestarian Koleksi Minangkabau Dinas Perpustakaan dan Kearsipan Kabupaten Tanah Datar - Wahyuni, Sri (Media Pustakawan, 2025)
Preservation activities play a vital role in maintaining the physical integrity of collections and ensuring the sustainability of the information they contain for continuous use. This study focuses on the application of the innovative GLAM (Gallery, Library, Archive, Museum) concept in preserving collections of local wisdom so that they can be enjoyed and utilized by the public. Another objective is to describe how an information management institution can integrate data from galleries, libraries, museums, and archives to help preserve Minangkabau cultural heritage. This research uses a qualitative method with purposive sampling techniques. Data collection methods include observation, interviews, and documentation. The results show that the implementation of the GLAM concept at the Library and Archives Office of Tanah Datar Regency has not been fully realized. In practice, the office has applied the GLA concept, as the museum is not yet part of the institution. The main challenges include a lack of public trust in the institution to submit their collections and limited human resources in preservation efforts. The study recommends collaboration with related institutions and local governments, as well as public outreach to raise awareness among both institution managers and the public about the importance of preserving local cultural heritage.